Ghana-EU economic partnership agreements - ASANTE-AGYEI, Ofori (KDI School, 2015)
This study sought to examine the trade creation and trade diversion effects that will emanate out from the signing and ratification of the Economic Partnership Agreements (EPAs) between Ghana and the EU. The EPAs being a bilateral trade agreement, guarantees a duty-free and quota-free market access on almost all product from Ghana to EU with a reciprocal market access of 85% of EU products into Ghana. The results of the regressions run establishes that there is an inverse relationship between remoteness and Ghana’s exports to the EU in that an increase in remoteness results in a decrease in Ghana’s exports and also an increase in inflation in importing countries (EU) results in a decrease in Ghana’s exports. In order to fully explore the welfare benefits which will emanate from the EPAs, the study recommends an effective implementation of the National Export Strategy. This strategy will deal with two main issues. These are the diversification of Ghana’s exports and an improvement in the business environment in Ghana.
Thesis(Master) --KDI School:Master of Development Policy,2015